Comparison of UK Curriculum with Malaysia Curriculum Zooming Into English for Lower Secondary (Year 7 and Form 1) (Sains Humanika, 2014)
The issue of English competency among Malaysians especially the younger generation continues to haunt our education system. Recently, the government has abolished the 40 per cent cap for local students to enrol in international schools nationwide â€œwith immediate effectâ€. This opens door for many parents who want an English medium education for their children. The reality is that there are already many foreign curriculums in the market. There are many private schools that run the UK Cambridge programme and American programme. The purpose of this study was to investigate the similarities and differences of the curriculums between UK and Malaysia for lower secondary by reviewing their overall curriculum aims and objectives specifically looking at a single English syllabus that caters for lower secondary learners. Since the UK Cambridge programme is implemented in Malaysia, the researcher also seeks to find out whether the curriculum matches our National Education Philosophy (NEP).This is a comparative document analysis research, which compares two documented English syllabus of two different countries. The researcher had also interviewed two teachers that are teaching the UK Cambridge Year 7 English and Malaysia Form One English.The principal conclusion was that both syllabuses have their own strength and limitation. While Year 7 English syllabus might be too hard for the general Malaysians Form One students but it provides a platform to challenge those with better English competency.
Keywords: Curriculum; English syllabus; secondary learner